Energy budget diagnosis of changing climate feedback - Cael,BB; Bloch-Johnson,J; Ceppi,P; Fredriksen,H-B; Goodwin,P; Gregory,JM; Smith,CJ; Williams,RG (Science Advances, 2023)
The climate feedback determines how Earth’s climate responds to anthropogenic forcing. It is thought to have been more negative in recent decades due to a sea surface temperature “pattern effect,” whereby warming is concentrated in the western tropical Pacific, where nonlocal radiative feedbacks are very negative. This phenomenon has however primarily been studied within climate models. We diagnose a pattern effect from historical records as an evolution of the climate feedback over the past five decades. Our analysis assumes a constant rate of change of the climate feedback, which is justified post hoc. We find a decrease in climate feedback by 0.8 ± 0.5 W m −2 K −1 over the past 50 years, corresponding to a reduction in climate sensitivity. Earth system models’ climate feedbacks instead increase over this period. Understanding and simulating this historical trend and its future evolution are critical for reliable climate projections.